Transformasi Edukasi Keuangan melalui Metode Gamifikasi bagi Siswa SDN 11 Pemecutan Denpasar - Helmy Syakh Alam; Eka Grana Aristyana Dewi; I Putu Shava Jaya Wardhana; Putu Rakhe Prabha Buana; Joshua Kevin Wijaya; Jelita Elisabeth Maak; I Kadek Subakti Kesuma (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
In the face of increasing financial complexity, providing elementary school students with fundamental financial literacy knowledge has become more imperative. Financial literacy is an essential life skill, but traditional teaching methods may not capture student's attention. This community service project sought to improve financial literacy among students at SDN 11 Pemecutan, Denpasar, through the gamification method